A Collaborative Scheduling System for Make-to-Order Manufacturing - Lee, K.I.; Kang, M.; Park, J.H. (1996)
In the make-to-order manufacturing industry, the details about the product specification become gradually known in phases from development, design, and process planning. This makes the production scheduling less accurate, and causes the operations schedule to be revised frequently during the manufacturing. To reconfigure the existing schedule, the monitoring data collected from the shop floor are essential. A collaborative scheduling system for the job shop has been developed to manage the job processing effectively. The system adopts presumptive, predictive and reactive scheduling methods. Each method is built into a module which performs scheduling based on the different data, and collaborates with other modules. The scheduling system is interfaced to a machine monitoring and data collection system. The experience of the implemented system in a factory is encouraging. ？ 1996 CIRP.
Keywords: Process control; Resource allocation; Scheduling; Cooperative job shop scheduling; Made to order manufacturing; Production control